انعكاسات وضعيات العمل على الصحة الجسمية للاستاذ دراسة ميدانية لعينة من الاساتذة بثانوية محمد الشريف بن شبيرة – بوسعادة - بلواضح نور الدين; اشراف: واضح العمري (جامعة محمد بوضياف -المسيلة, 2025)
تهدف هذه الدراسة الى معرفة انعكاسات وضعيات العمل على الصحة الجسمية للاستاذ ، ولتحقيق هدف البحث اعتمدنا المنهج الوصفي التحليلي ، كما تم اعداد استبيان مكون من 42 فقرة ، يشمل بنودا من استبيان نورديك للصحة العضلية الهيكلية ، (كورنيوكا،1978) وبنودا من استبيان صحة الجهاز العضلي الهيكل Q-MSK ، Arthritis Research UK,2018)) وبنودا من اعداد الطالب ،تم جمعها في المرحلة الدراسة الاستطلاعية عن طريق الملاحظة تشمل وضعيات العمل المختلفة . بعد التاكد من صدق الاستبيان و ثباته ، وعرضه على مجموعة من المحكمين تم تطبيقه على عينة البحث تشمل( 58 استاذ من كلا الجنسين ) من ثانوية الشريف محمد بن شبيرة ببوسعادة، من أصل 82 استاذ ، وبعد المعالجة الإحصائية أسفرت النتائج عما يلي: • توجد انعاكسات لوضعيات العمل على الصحة الجسمية لعينة الدراسة،بمستوى أقل من المتوسط. • تاثير وضعية الوقوف على الصحة الجسمية للاساتذة على أسفل الظهر بمستوى أقل من المتوسط. • تأثير رفع اليد الى مستوى أعلى من الكتف أثناء الكتابة على السبورة على الكتف بمستوى أقل من المتوسط. • عدم وجود فروق ذات دلالة إحصائية بين أفراد العينة في درجة تأثير وضعيات العمل على الصحة الجسمية تبعا لمتغير الجنس. • عدم وجود فروق ذات دلالة إحصائية بين أفراد العينة في درجة تأثير وضعيات العمل على الصحة الجسمية تبعا لمتغير السن . • عدم وجود فروق ذات دلالة إحصائية بين أفراد العينة في درجة تأثير وضعيات العمل على الصحة الجسمية ،تبعا لمتغير الأقدمية في العمل. • توجد انعاكاسات لوضعيات العمل على الوضع الصحي العام لعينة الدراسة بمستوى متوسط الكلمات المفتاحية: (انعكاسات – وضعيات العمل – الصحة الجسمية – الاستاذ) This study aims to investigate the impact of working postures on the physical health of teachers. To achieve this objective, the descriptive-analytical method was adopted. A questionnaire consisting of 42 items was developed, incorporating elements from the Nordic Musculoskeletal Questionnaire (Kourinka, 1978), the Q-MSK Musculoskeletal Health Questionnaire (Arthritis Research UK, 2018), and items prepared by the researcher, based on observations conducted during the exploratory study phase, which included various working postures. After confirming the questionnaire's validity and reliability, and having it reviewed by a panel of experts, it was administered to a sample of 58 teachers (both male and female) from the Cherif Mohamed Ben Chabira Secondary School in Bou Saada, out of a total population of 82 teachers. Statistical analysis of the data yielded the following results: • Working postures have an impact on the physical health of the sample, but at a below-average level. • Standing posture affects the lower back health of teachers, also at a below-average level. • Raising the hand above shoulder level while writing on the board affects the shoulder, again at a below-average level. • There are no statistically significant differences in the impact of working postures on physical health based on gender. • There are no statistically significant differences based on age. • There are no statistically significant differences based on years of work experience. • Working postures have a moderate level of impact on the general health status of the study sample. Keywords:( Impacts – Working Postures – Physical Health – Teacher)